CORRELATION OF VASCULAR ENDOTHELIAL FUNCTION AND INFLAMMATORY FACTORS WITH RENAL FUNCTION IN PATIENTS WITH DIABETIC NEPHROPATHY - Mammadzada, A.Y.; Ismayilova, Sh.G.; Ibrahimova, Sh.S.; Huseynova, N.I.; Huseyn, L.A. (World of Medicine and Biology, 2023)
The purpose of the study was to examine the interrelation between vascular endothelial function and inflammatory factors with renal function in patients diagnosed with diabetic nephropathy. A total of 120 patients with diabetic nephropathy were enrolled in this study. The patients were categorized based on the stage of diabetic nephropathy: Group I – normoalbuminuria (n=30), Group II – microalbuminuria (n=30), Group III – macroalbuminuria (n=30), Group IV – patients with clinical nephropathy (n=30). The levels of creatinine, endothelin-1, nitric oxide, interleukin-6, interleukin-10, tumor necrosis factor-alpha in the blood and glomerular filtration rate were determined. There was a correlation between glomerular filtration rate and blood endothelin-1 (r=0.517 (p
Keywords: diabetic nephropathy; glomerular filtration rate; interleukin; endothelin-1; tumor necrosis factor-alpha